UPAYA GURU BIMBINGAN KONSELING DALAM MENGATASI KEBIASAAN MEROKOK MELALUI BIMBINGAN KELOMPOK DI SMA AL-HIDAYAH MEDAN - Siti Mawaddah Hasibuan (UIN Sumatera Utara, 2020)
This study aims to determine and describe the efforts of guidance and counseling teachers in overcoming smoking habits in Al-Hidayah Medan High School and to know and explain the obstacles faced by guidance and counseling teachers. And knowing and describing the solutions provided by the guidance and counseling teacher in overcoming smoking habits in Al-Hidayah Medan High School. The method in this study is qualitative research, the subjects in this study are people who are sampled in a study that is the principal, 1 BK teacher and some students. Data collection techniques through observation, interviews and documentation. As for data analysis techniques used, namely data reduction (data collection), data presentation and drawing conclusions. The data validity technique is carried out with credibility, transferability, dependability and confirmability. The results of the study are the efforts of BK teachers to be needed at Al-Hidayah Medan High School. As for the obstacles faced by BK teachers in handling smoking students in the form of BK teachers do not have special BK hours, communication between BK teachers and parents / guardians of students does not run smoothly. , and the difficulty of students to be invited by group guidance to. And the Solutions in handling the constraints that exist in schools include mutual communication with fellow teachers in the school, both the BK teacher with the principal and with other teachers. Keywords: Efforts, Smoking Habits.